Perilaku Narsisme dan Harga Diri Terhadap Penggunaan Media Sosial Tiktok Pada Siswa SMA - Lidyamega Handari Putri (Universitas PGRI Semarang, 2021)
Abstract. The number of students accessing the internet every year makes any changes that occur in adolescence which can cause certain problems in him. ideally adolescents are able to develop well, not displaying behavior that leads to negative behavior. Narcissists are very self-centered, always emphasize that they are perfect (self-congratulatory), and see their desires and hopes as important things. Self-esteem affects the use of social media in a teenager seen when publishing himself by displaying photos or videos that are considered attractive and tend to be indifferent. This study aims to examine the relationship between narcissistic behavior and self-esteem on the use of Tiktok social media. The sampling technique used is proportioned random sampling, total sample 213 with data collection using a psychological scale. The data analysis technique uses multiple linear regression by showing the results of a positive and significant relationship between narcissistic behavior and self-esteem on the use of TikTok social media with a significance result of 0.000 <0.05 and a calculated F value of 11.027> table 2.14Keywords: (Narcissists, Self-esteem, Tiktok social media)